16 Y/O Female with “Watermelon Stomach”? - Amandeep Singh; Anwaar A. Khan; Robert Krall; Zafar K. Mirza (Case Reports in Medicine)
Background. Gastric antral vascular ectasia (GAVE) also known as “watermelon stomach” (WS) is an uncommon cause of gastrointestinal (GI) blood loss. It typically presents in middle aged females. We are presenting a case of GAVE at an unusually early age with atypical symptoms. Case. A previously healthy 16 y/o Caucasian female presented to the ER with a one-month history of upper abdominal pain. Physical examination was benign except tenderness in the epigastric region. There were no significant findings on laboratory data. Upper endoscopy showed incidental findings of linear striae in the antrum indicative of GAVE but histology was equivocal. Discussion. GAVE is a poorly understood but treatable entity and an increasingly identifiable cause of chronic iron deficiency anemia or acute or occult upper GI bleeding. The pathophysiology of GAVE remains unclear. It is an endoscopic finding characterized by longitudinal columns of tortuous red ectatic vessels (watermelon stripes), pathognomonic for WS. Treatment options include endoscopic, pharmacologic, and surgical approaches. Failure to recognize GAVE can result in delayed treatment for years. Our patient with GAVE was unusually young and was diagnosed incidentally. Due to lack of anemia on laboratory examination we elected to monitor her clinically for any future development of anemia.